Bank ownership type and banking relationships - Berger, Allen N.; Klapper, Leora F.; Martinez Peria, Maria Soledad; Zaidi, Rida (Journal of Financial Intermediation, 2008)
We formulate and test hypotheses about the role of bank ownership type—foreign, state-owned, and private domestic banks—in banking relationships. Our application uses data from India, an important developing nation. The empirical results are consistent with all of our hypotheses with regard to foreign banks. First, these banks tend to establish relationships with relatively transparent firms. Second, firms that have relationships with foreign banks are more likely to enter into multiple banking relationships and to maintain a larger number of such relationships. Finally, firms banking with foreign banks are more likely than others to diversify relationships across bank ownership types. The data are also consistent with the hypotheses that firms with relationships with state-owned banks are relatively unlikely to maintain multiple banking relationships, tend to interact with a smaller number of banks, and less often diversify across ownership types.